Patient- and Caregiver-Reported Experiences of Rare Diseases in Türkiye: A Patient-Organization-Recruited Online Survey - Murat Gülşen; Hikmet Can Çubukçu; Onur Burak Dursun; Hayri Canbaz; Sıddika Songül Yalçın (Journal of Clinical Medicine, 2026)
Background and Objectives: Rare diseases collectively affect large populations and require coordinated, patient- and caregiver-informed health and social support. This study had an overarching descriptive objective to characterize patient- and caregiver-reported experiences of living with rare diseases in Türkiye and a secondary exploratory objective to assess differences across broad disease categories. Materials and Methods: This cross-sectional, anonymous, voluntary non-probability online survey recruited affected individuals and relatives/caregivers through patient-organization networks. The 44-item questionnaire covered sociodemographic and caregiving context, diagnostic experiences, psychosocial support, healthcare access, and service-improvement priorities. Descriptive analyses, exploratory disease-group comparisons, Cramér’s V, and selected multivariable logistic regression models were used. Results: A total of 1642 responses were analyzed; 76.7% were completed by relatives/caregivers, and 66.4% concerned patients younger than 18 years. Among participants diagnosed after symptom onset (n = 1388), 34.4% reported an incorrect or alternative diagnosis and 64.0% sought at least one additional specialist opinion. Psychosocial support was needed by 74.2%, whereas 34.5% reported receiving professional support. Access to current treatment services was perceived as moderately adequate by 29.3% and adequate by 13.0%. The leading service-improvement priorities were increasing healthcare professionals’ knowledge (82.9%) and establishing specialized rare-disease centers (79.5%). Conclusions: This patient-organization-recruited survey provides a large descriptive account of the experiences and priorities reported by participating patients and caregivers. The findings identify perceived priorities, particularly clinician education and specialized centers, while not constituting nationally representative estimates.